Iteration of quadratic maps on coquaternions - Falcão, M. I. (2017)
This paper is concerned with the study of the iteration of the quadratic coquaternionic map fc(q) = q2 + c, where c is a fixed coquaternionic parameter. The fixed points and periodic points of period two are determined, revealing the existence of a type of sets of these points which do not occur in the classical complex case: sets of nonisolated points. This brings the need to consider a different concept of stability. The analysis of the stability, in this new sense, of the sets of fixed points and periodic points is performed and a discussion of certain type of bifurcations which occur, in the case of a real parameter c, is also presented.